Penguatan Kelompok Teman Sebaya dalam Pencegahan Bullying di Lingkungan Sekolah - Bahrul Amsal; Ulfa Utami Mappe; Idham Irwansyah; Sunaniah Sunaniah; Salwiah Salwiah (Universitas Negeri Makassar, 2024)
The PKM program is carried out by providing socialisation materials for participants regarding the understanding and prevention of bullying in the school environment with the aim of (1) increasing knowledge about bullying by forming peer groups, (2) participants can properly implement bullying prevention efforts through peer groups in the process of activities at school, and (3) participants can disseminate knowledge about the dangers of bullying in the school environment through peer groups. The main target audiences of the PKM Programme activities are school supervisors, principals, school teachers, and students at UPT SD Negeri Kakatua Makassar. The results obtained in the PKM programme activities are increased knowledge and concepts of peer group-based bullying prevention, increased understanding of the flow of prevention and reporting if they find bullying events at school, and PKM programme participants can implement their own attitudes so as not to become bullying perpetrators in the school environment and community environment. The outputs of the PKM activities are (1) increased knowledge of participants about the activity materials, (2) scientific articles published at national seminars, and (3) publication of PKM implementation in online media.